Ability of Gutta-Percha and Resilon to Fill Simulated Lateral Canals by Using the Obtura II System - Tanomaru-Filho, Mario [UNESP]; Sant'Anna-Junior, Arnaldo [UNESP]; Berbert, Fabio Luis C. V. [UNESP]; Bosso, Roberta [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Elsevier B.V., 2012)
Introduction: The aim of this study was to evaluate the ability of Resilon (Resilon Research, LLC, North Branford, CT) and 2 types of gutta-percha to fill simulated lateral canals when using the Obtura II system (Model 823-700; Obtura Spartan, Fenton, MO). Methods: Forty-five human single-rooted teeth were selected and subjected to root canal preparation. After that, simulated lateral canals were made at 2, 5, and 8 mm from the working length (WL). The specimens were divided into 3 groups (n = 15) according to the filling material used: Obtura Flow 150 gutta-percha (Obtura flow), Odous Endo Flow gutta-percha (Odous; Odous de Deus Ind e Corn. Ltda Belo Horizonte, MG, Brazil), and Resilon pellets (Resilon). Root canals were filled using the Obtura II system with the tip inserted to 3 mm from the WL. No sealer was used for root canal obturation. Specimens were subjected to a tooth decalcification and clearing method, and filling of the lateral canals was analyzed by digital radiography and photographs. The measurement of lateral canal filling was done using Image Tool software (UTHSCSA Image Tool for Windows version 3.0, San Antonio, TX). Data were statistically analyzed with the Kruskal-Wallis test at 5% significance. Results: All materials showed an ability to penetrate into the simulated lateral canals, with a minimum percentage of 73% in all thirds of the root canal. Conclusions: It was concluded that gutta-percha and Resilon are solid core materials with a lateral canal filling ability when used with the Obtura II system. (J Endod 2012;38:676-679)
Keywords: Gutta-percha; lateral canals; Resilon; root canal filling material